PROCEDURAL SEDATION AND ANALGESIA FOR ERCP: A COMPARATIVE STUDY OF THE PROPOFOL AND KETAMINE–PROPOFOL COMBINATION (KETOFOL) - Nadia Bano; Shahid Rasool; Ahmed Raza (Journal of University Medical & Dental College, 2016)
ABSTRACT:OBJECTIVE: The aim of this study was to ﬁnd a near ideal drug for procedural sedation and analgesia for patients undergoing ERCP.STUDY DESIGN: A randomized control study was carried out for comparison.SETTING & DURATION: This study was conducted at department of anaesthesia and intensive care, Madinah Teaching Hospital, Faisalabad from August 2014 to July 2015.SAMPLE SIZE: The group under study consisted of 146 ASA I & II status patients undergoing ERCP.METHODS: The patients were randomly divided into two groups A and B. Group A patients were to receive Propofol and Group B patients were to receive Ketamine-Propofol (Ketofol).RESULTS: As compared to Propofol Group (group A), Ketofol group (group B) showed signiﬁcant hemodynamic stability. The frequency of hypotension was 27.4% in group A as compared to 12.3% in group B. Respiratory drive was maintained in both groups. Requirement for post procedure analgesia was signiﬁcant in group A being 16.4% as compared to 2.7% in group B. Time of onset and oﬀset were also signiﬁcantly shorter in group B.CONCLUSION: It is concluded that Ketofol oﬀers stable hemodynamics, adequate sedation and analgesia for patients undergoing ERCP. It also oﬀers quick onset and oﬀset of sedation. So it is a near ideal agent for procedural sedation and analgesia for ERCP.